Wet-lab practice on goat's eye: a postgraduate's perspective - Vidha, Aditi (Research and Humanities in Medical Education, 2020)
People see the world through their eyes. The world gets blurred if their vision gets blurred. As ophthalmologists, the onus of care falls on us. What makes ophthalmology different from other surgical branches is that it is a delicate surgery and is challenging for the ophthalmology professors to teach the surgeries and postgraduates to learn the same. So the concept of wetlab is introduced in many colleges where a goat's eye is used to practice skills of surgery before an actual hands-on experience on human eyes. In this narrative, I share my experiences as a postgraduate student in the wetlab using a goat's eye for learning cataract surgery. The journey commences from first hearing about goat's eye, to acquiring it, to using it, and ends with the opportunity to work on human eyes.